Techniques used to formulate confidential data by means of fragmentation and hybrid encryption - Beckham, Olly; Oldman, Gord; Karrie, Julie; Craig, Dorth (International research journal of management, IT and social sciences, 2019)
Cloud computing is a concept shifting in the approach how computing resources are deployed and purchased. Even though the cloud has a capable, elastic, and consistent design, several security concerns restrain customers to completely accept this novel technology and move from traditional computing to cloud computing. In the article, we aspire to present a form of a novel architectural model for offering protection to numerous cloud service providers with the intention to devise and extend security means for cloud computing. In this work, we presented a two-tier architecture for security in multi-clouds; one at the client side, and other at the server side. The article presented a security domination outline for multi-clouds and supports security needs like Confidentiality, Integrity, Availability, Authorization, and Non-repudiation for cloud storage. Through this document we have anticipated, HBDaSeC, a secure-computation protocol to ease the challenges of enforcing the protection of data for information security in the cloud.